MIXING OF INDONESIAN ADDRESSING TERMS IN THE LOCAL ENGLISH: MOTIVATIONS AND IDENTITY EXPRESSIONS - Chandra, Patricia Cynthia; Bhimasena, Harya; Ekarina (Masyarakat Linguistik Indonesia, 2024)
This study is concerned with the effect of globalization on language usage, especially in the context of the Indonesian workplace. Within the context of international workplaces where employees often use English to communicate with their foreign colleagues, the researchers found that Indonesian addressing terms such as Pak or Bu are often mixed in with English. This study considers this phenomenon typical in high language contact situations; and sees the mixing of some Indonesian in the English spoken in Indonesia as a distinct characteristic of the localized English used in the country. Specific patterns and motivations for such mixing of the Indonesian addressing terms in the local English may uncover certain identity expressions by Indonesians as a reaction to globalization. To explore these issues, interviews were conducted with employees of international workplaces in Indonesia to determine: (i) different motivations for mixing Indonesian addressing terms in the local English, and (ii) what the different motivations may reveal about the identities of different Indonesian speakers. Results from the interview reveal that the use of Indonesian addressing terms and the related speakers’ identities are largely dependent on social class.